2020
DOI: 10.1016/j.omtm.2019.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Infant and Adult Mice Reveal Age Effects for Liver Depot Gene Therapy in Pompe Disease

Abstract: Pompe disease is caused by the deficiency of lysosomal acid α-glucosidase (GAA). It is expected that gene therapy to replace GAA with adeno-associated virus (AAV) vectors will be less effective early in life because of the rapid loss of vector genomes. AAV2/8-LSPhGAA (3 × 1010 vector genomes [vg]/mouse) was administered to infant (2-week-old) or adult (2-month-old) GAA knockout mice. AAV vector transduction in adult mice significantly corrected GAA deficiency in the heart (p < 0.0001), diaphragm (p < 0.01), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 44 publications
(112 reference statements)
0
18
0
Order By: Relevance
“…The reduced transduction efficiency in the liver observed with injection via the retro-orbital route is an additional argument for this hypothesis. Since the retro-orbital injection can already be carried out accurately in 3-week-old mice, juvenile mice were used in order to minimize the distribution volume of the vector solution as much as possible although it has been reported that the AAV vector transduction is more stable in adult animals [ 12 ]. Indeed, a ~90% reduction in TRPM4 protein expression was achieved with the latter approach.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced transduction efficiency in the liver observed with injection via the retro-orbital route is an additional argument for this hypothesis. Since the retro-orbital injection can already be carried out accurately in 3-week-old mice, juvenile mice were used in order to minimize the distribution volume of the vector solution as much as possible although it has been reported that the AAV vector transduction is more stable in adult animals [ 12 ]. Indeed, a ~90% reduction in TRPM4 protein expression was achieved with the latter approach.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, supraphysiological GAA levels did not result in glycogen depletion below physiological levels, even at the highest dose of AT845. Glycogen levels, which are inherently higher in diaphragm compared with heart or skeletal muscle in this mouse model (Keeler et al , 2019; Han et al , 2020), can fluctuate up to 100% daily (Gomes et al , 2009). High glycogen levels in some mice may reflect time of euthanasia.…”
Section: Discussionmentioning
confidence: 94%
“…WBP quantifies minute ventilation, lung volumes, and changes in flow in awake, spontaneously breathing mice [44,51,70]. WBP studies confirm that mouse models of Pompe disease have respiratory dysfunction [42,45,49,51,52,61,63,71,72]. Although results of WBP at baseline vary, most studies found that Gaa −/− mice have abnormal parameters of WBP.…”
Section: Respiratory Pathophysiology In the Gaa −/− Mouse Modelmentioning
confidence: 99%
“…While breathing room air (FiO 2 0.21; N 2 balance), these mice have greater expiratory time (Te) [45] and lower tidal volume (TV) [49,63], frequency (f) [45,49], tidal volume to inspiratory time ratio (TV/Ti) [49,61], minute ventilation (VE) [49], minute ventilation to expired CO 2 ratio (VE/V CO2 ) [49,61], peak inspiratory flow (PIF) [49,61], and peak expiratory flow (PEF) [49,71]. Furthermore, during a hypercapnic challenge (FiCO 2 : 0.07; FiO 2 0.21; nitrogen balance), Gaa −/− mice on both the B6/129 and the 129SVE backgrounds have a reduced response to respiratory challenge [42,49,51,[61][62][63]71,72]. For example, these mice have lower VE, TV, and PIF relative to WT during hypercapnic challenge, although these factors did increase relative to baseline [42,49,51,[61][62][63]71].…”
Section: Respiratory Pathophysiology In the Gaa −/− Mouse Modelmentioning
confidence: 99%